Accounting system and operation of Islamic Insurance: case study on Syarikat Takaful Malaysia Sendirian Berhad / Anizan Abu Hassan - Abu Hassan, Anizan (1992)
Modern living and business activities in general involve the risk of sustaining losses of varying type and degree. One of the measures adopted in modern times for the organisation of economy and finance is insurance. It has a key role in present industrial development as well as in large-scale organisation of commerce, industry and agriculture.